2020
DOI: 10.1177/1528083720947734
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nonwoven structure on thermomechanical properties of feather waste reinforced polyester composite

Abstract: Natural fibers offer good prospective as reinforcements in polymer composites due to their superior properties, they are preferred over synthetic fibers in various applications such as construction, automotive and aerospace. This experimental study emphasizes the effect of nonwoven structure on the mechanical, thermal and biodegradability properties of feathers nonwoven reinforced polyester composite. Vacuum molding method was adopted for manufacturing of the biocomposites with two contents of polyester resin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…65 Despite this, the thermal conductivity values of composites reinforced with a nonwoven structure are significantly lower than those of composites reinforced with fibers (see Table 5), indicating that the produced composites are excellent thermal insulators for automotive and construction applications. 66,67
Figure 14.Thermal conductivity of developed materials.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Despite this, the thermal conductivity values of composites reinforced with a nonwoven structure are significantly lower than those of composites reinforced with fibers (see Table 5), indicating that the produced composites are excellent thermal insulators for automotive and construction applications. 66,67
Figure 14.Thermal conductivity of developed materials.
…”
Section: Resultsmentioning
confidence: 99%
“…65 Despite this, the thermal conductivity values of composites reinforced with a nonwoven structure are significantly lower than those of composites reinforced with fibers (see Table 5), indicating that the produced composites are excellent thermal insulators for automotive and construction applications. 66,67 The use of untreated and sol-gel treated nonwovens into a polymer matrix may cause some impacts on the thermal properties of the resulting composites that are important parameters in processing and application of materials. The thermal stability of neat polyester and its composites were evaluated by TGA and shown in Figure 15.…”
Section: Thermal Characteristics Of Composite Materialsmentioning
confidence: 99%
“…There is little evidence in the literature regarding the biodegradability of nonwovens with the addition of feather waste. Mrajji et al [41] investigated the effects of nonwoven structures on the mechanical, thermal and biodegradability properties of feather-based nonwoven materials that were reinforced by polyester composites. The obtained results showed that the introduction of feather waste into the matrix slightly reduced the degradation process time.…”
Section: Discussionmentioning
confidence: 99%
“…This table highlights fibres used in at least two instances across the reviewed documents. Other fibres that were used in only one study include African walnut shell (Nigeria), 85 ampelocissus cavicaulis (Nigeria), 86 cassava cortex (Nigeria), 87 chicken feathers (Morocco), 88 cissus populnea (Nigeria), 89 coffee husk (Ethiopia), 90 combretum dolichopetalum (Nigeria), 91 cyanara cardunculus L. (Algeria), 92 dioscorea alata (Nigeria), 93 diss grass (Algeria), 94 egg shell (Nigeria), 95 el retma (Algeria), 96 eucalyptus capsule (Morocco), 97 grapevine (Tunisia), 98 groundnut shell (Nigeria), 99 Mediterranean saltbush (Algeria), 100 Nacha–hibiscus (Ethiopia), 101 natural cork (Tunisia), 102 orange peels (Algeria), 103 posidonia oceanica (Tunisia), 104 raw pepper (Morocco), 105 reed fibres (Egypt), 106 screwpine (Mauritius), 107 sunflowers trimmings (Egypt), 108 teff straw (Ethiopia), 109 and triumfetta cordifolia (Cameroon) 110 …”
Section: Fibres Sourced From Africamentioning
confidence: 99%